Public Transport/Public Transit (A97-A104)A97 New metro line in Turin: an analysis of the impacts on local mobility and road traffic accidents. Issue 2 (June 2015) - Bianco, Selene; Melis, Giulia; Eynard, Enrico; Marietta, Cristina; Tabasso, Matteo; Mamo, Carlo; Costa, Giuseppe
Abstract: Background: Several studies have analysed impacts of new metro lines in dense urban areas. This transport mode is able to move travellers from private car to a more efficient and less time-consuming solution. This shift determines lower traffic congestion rates, leading to reduced traffic accidents. Few studies have also applied an equity lens, to understand who is really benefitting from these improvements: results show that ethnic minorities, economically disadvantaged, children and women are the most exposed to injuries. Methods: We analyse impacts of the construction of the last metro section in Turin (Italy), highlighting effects during the construction phase, and after the opening. We analyse data on road traffic injuries in relation to the improved accessibility offered by the metro line, and how impacts are distributed among the population. We considered an impact area of 500 m around subway stations. Time series (2004-2013) of road traffic accidents in the whole city has been compared to the one of accidents occurred in the selected area (pre-during-post intervention). A Bayesian change-point (BCP) approach has been used to identify where each time series undergoes sudden changes. Finally, a Poisson regression analysis has been performed in order to verify if road accidents in the subway area have a significantly greater reduction than the ones occurred in the whole city. Results: BCP algorithm shows that the trend of road traffic accidents in the subway area had an increase in august 2006, and then decreased at the beginning of 2008. Taking the whole city as comparison, we can notice a reduction in the beginning of 2008 but no significant change around 2006. Moreover, the Poisson regression showed no significant reduction of accident rates in the area when compared to the whole city in the period 2004-2013. When considering only the main street of the subway line (via Nizza), the model showed a more marked reduction, accompanied by a car traffic reduction of 3%. Conclusions: While the opening in 2006 of the first section of the Turin metro significantly reduced injuries from road accidents on the corresponding area, preliminary results for this last section seem to indicate a modest impact. The increase of accidents in the subway area from august 2006 can be related to the opening of working sites, and consequent traffic deviations. Shift of travellers from private car to underground has not been wide as expected. The missing interconnection with other transport modes could partly explain this.